Isoquercitrin from Apocynum venetum L. produces an anti-obesity effect on obese mice by targeting C-1-tetrahydrofolate synthase, carbonyl reductase, and glutathione S-transferase P and modification of the AMPK/SREBP-1c/FAS/CD36 signaling pathway in mice in vivo. Issue 21 (7th October 2022) - Manzoor, Majid; Muroi, Makoto; Ogawa, Naoko; Kobayashi, Hiroki; Nishimura, Haruna; Chen, Danni; Fasina, Opeyemi B.; Wang, Jianyu; Osada, Hiroyuki; Yoshida, Minoru; Xiang, Lan; Qi, Jianhua
Abstract : In the present study, mice with high-fat-diet-induced obesity were used in investigating the anti-obesity effects of an aqueous extract and isoquercitrin from Apocynum venetum L. Abstract : In the present study, mice with high-fat-diet-induced obesity were used in investigating the anti-obesity effects of an aqueous extract and isoquercitrin from Apocynum venetum L. The aqueous extract and the signal molecule isoquercitrin significantly reduced the body weight gain, food intake, water consumption, and fasting blood glucose, plasma triglyceride and total cholesterol levels of the obese mice. Furthermore, the mechanism of action of isoquercitrin was explored through RT-PCR analyses and uptake experiments of adenosine 5′-monophosphate-activated protein kinase (AMPK) and sterol regulatory-element binding protein (SREBP-1c) inhibitors and glucose. The indexes of SREBP-1c, fatty acid synthase (FAS), stearoyl-CoA desaturase-1 (SCD), and cluster of differentiation 36 (CD36) in obese mice significantly increased but returned to normal levels after the administration of isoquercitrin. Meanwhile, the anti-obesity effect of isoquercitrin was diminished by the inhibitors of AMPK and SREBP-1c. In addition, intestinal glucose uptake in normal mice was significantly inhibited after the oral administration of isoquercitrin. Moreover, 2D gel electrophoresis based proteome-wide cellular thermal shift assay (CETSA) showed that the potential target proteins of isoquercitrin were C-1-tetrahydrofolate synthase, carbonyl reductase, and glutathione S -transferase P. These results suggested that isoquercitrin produces an anti-obesity effect by targeting the above-mentioned proteins and regulating the AMPK/SREBP-1c signaling pathway and potentially prevents obesity and obesity-related metabolic disorders.